Dynamic responses of a hinged-hinged Timoshenko beam with or without a damage subject to blast loading - Metsebo, J.; Nana Nbendjo, B.R.; Woafo, P. (Mechanics research communications, 2016)
•Damage forecast in a hinged-hinged Timoshenko beam subjected to blast excitation.•The damage function take into account the spatial repartition of the damage along the beam.•Numerical simulation of damaged PDE Timoshenko beam is performed.•The reaction deflection analysis show the risk of shear failure according to the damaged state.•The dynamics of the damaged and healthy states allow to foresee the degree of the damage. The present paper addresses the subject of dynamics and damage detection in Timoshenko beam subjected to blast excitation. The general equation governing the dynamics states of both healthy and damaged hinged-hinged Timoshenko beam is derived. A damage function evolving the location, the sizes, the geometry of the damaged area is proposed and the response to blast loading is investigated. The exploration and the comparison of the dynamics of the damaged and healthy states allow to foresee the degree of the structural damage.